Age-specific serum prostate-specific antigen references range among healthy men in Port Harcourt, Nigeria: a retrospective hospital-based study - Amadi, Collins; Odum, Ehimen P. (International Journal of Research in Medical Sciences, 2018)
Background: Total prostate-specific antigen (PSA) levels increase with advancing age. Its age-specific ranges are being advocated to increase its sensitivity and specificity. This study was aimed to examine the relationship between total PSA levels and age, and to determine the age-specific ranges among healthy men without prostatic diseases in our environment. Methods: In this retrospective hospital-based study, records of men without prostatic diseases who had visited University of Port Harcourt Teaching Hospital for routine screening for prostate cancer using serum total PSA between 1st January 2012 and 31st December 2016 were retrieved and analyzed using descriptive statistics and Spearman’s correlation test. A p-value < 0.05 was considered significant. Results: Records of 476 men aged 38 to 86 years were recruited for the study. The age-specific total PSA reference range using the 95th percentile total PSA concentration values in each 10year groups were 0-1.60, 0-4.93, 0-6.93, 0-7.80, 0-9.65, and 0-13.30 for the age groups 30-39, 40-49, 50-59, 60-69, 70-79 and >80years respectively. There was a positive correlation between serum PSA concentration and age (rs = 0.395; p<0.001). Conclusions: Total PSA increases with advancing age and its age-specific reference range in this study are similar to findings in our environment but higher than the values found in other parts of the world. We suggest serum PSA normal reference values should be characterized by age and race in our environment.